Al-modified SBA-15 confinement of coal tar pitch for bifunctional N/S-doped porous carbon electrocatalysts - Chunlei Zhang; Xinxin Pi; Yanhui Li; Yunkai Wang; Mengjin Wen; Chengrui Wang; Huimin Feng; Yan He (Fuel, 2027)

Rapid and sensitive on-site detection of PBoV G3 using an EsCas13d-based platform - Peng-fei Fu; Zhuo-wei Zhang; Jun Hong; An-xin Hu; Yi-yang Shi; Jia-wen Lin; Si-yi Pi; Yu-yan Zhang; Yan-hong Wang; Min Lu; Guo-you Yin; Dong-mei Wang (Analytica Chimica Acta, 2026)

In vitro regeneration via indirect organogenesis from aseptic seedling-derived explants of the rare Tibetan medicinal shrub Sibiraea angustata - Mengting Pi; Xue Yu; Hongchang Li; Yali Guo; Wuyang Lai; Leipeng Cao; Tao Jiang; Lingxia Xu; Fuhua Peng; Hongdong Liu; Fei Wang; Jianguo Hu; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Disruption of ADAMTSL4 Causes Ectopia Lentis et Pupillae in Human and Zebrafish via Zonular Anchorage Defects and COL8A1-Driven Cell Migration - Xinyi Huang; Wannan Jia; Xin Shen; Xinyao Chen; Yalei Wang; Qiuyi Huo; Tianhui Chen; Min Zhang; Keji Jiang; Xuqing Gao; Guangqi A; Fengjing Yang; et al. (Phenomics, 2026)

Comprehensive multi-omics analysis reveals key metabolites and lipids driving flavor development in quail egg yolk - Cui Ma; Xiaoyue Yu; Hao Zhang; Yuejin Pu; Jinsong Pi; Yan Wu (Food Chemistry, 2026)

The inhibition of the AMPK and PPAR signaling pathways may be involved in the metabolic disorder of large yellow croaker induced by Pseudomonas plecoglossicida ppTse6 - Huan-jiao Tan; Yu-jia Sun; Xi-zhi Peng; Qing-pi Yan (Fish & Shellfish Immunology, 2026)

Two new species of Impatiens subg. Clavicarpa from southern China - Tian Hu; Kan-Ying Qiu; Pi-Ning Zhou; Yi-Yan Cong; Guang-Wan Hu (Plant Systematics and Evolution, 2026)

Structural characteristics and oxidative stability of diacylglycerols prepared from Huajiao seed oil - Xiaowei Peng; Chi Zhang; Ting Wang; Yan Pi; Jianquan Kan (Food Chemistry, 2026)

Methane biogeochemical turnover constrains arsenic transformation in groundwater systems: Organic molecular signatures and microbial functional networks - Xianjun Xie; Enyu Li; Honglin Jiang; Kunfu Pi; Lu Yan; Shuai Shen (Water Research, 2026)

Hierarchical carbon electrocatalysts with atomic Co-N/Pyridinic-N synergy for efficient bifunctional oxygen reactions - Jian Li; Zongqi Zhao; Xinxin Pi; Guangshun Chai; Lingtao Ran; Chunlei Zhang; Yanhui Li; Junhan He; Keke Zhang; Yan He (Fuel, 2026)

The application of magnetic therapy in stroke treatment: Traditional treatment and biomaterials - Yi Fan; Xinyu Zhang; Lei Zhang; Xiaoyu Han; Haitong Zhao; YuJie Zhong; Xuan Jiang; Yutian Wei; Yan Pi; Yunyan Wang; Xinyi Yao; Yuge Ye; et al. (Chemical Engineering Journal, 2026)

CYP450 activation and mitophagy induction mediate Ti3C2 MXene detoxification in RAW 264.7 cells - Yujiao Liu; Xuan Mao; Yongyi Wei; Xiaodi Li; Jianbo Jia; Qingmeng Liu; Jian Liu; Yu Wang; Xiaofei Zhou; Huihui Wang; Jingbo Pi; Guangbo Qu; et al. (Journal of Hazardous Materials, 2025)

Changes in ferroptosis-related molecular expression in macrophages of community-acquired pneumonia patients and their associated with the disease progression - Huan-Shao Huang; Jia-Xin Chi; Le-Yao Xiao; Jia-Jun Wang; Shi-Ying Lai; Lan Chen; Jiang Pi; Yan-Guang Cong; Yi-Ming Shao; Jun-Fa Xu (Inflammation Research, 2025)

Methane removal performances and microbial responses in surfactant-enhanced biotrickling filters - Xin Wu; Liangkai Wu; Zhoujie Pi; Chunping Yang; Xiaobo Tan; Yan Lin (Journal of Environmental Chemical Engineering, 2025)

Comparative analysis of phytoplankton community structure and stability in the Arabian Sea and Bay of Bengal using eDNA metabarcoding - Changwen Li; Ge Xiao; Han Long; Tongxi Ai; Fenghua Tang; Jianfeng Ju; Shenglong Yang; Yan Pi; Lei Gao; Lingbo Ma; Wei Fan; Ming Zhao; et al. (Marine Environmental Research, 2025)

Enhancing removal performance of ciprofloxacin hydrochloride by Chlorella vulgaris-bacteria consortium: Insights of microbial responses and stoichiometry - Yongrui Pi; Yan Li; Wenpeng Jia; Yongzheng Tang (Journal of Hazardous Materials, 2025)

Leaching model of an expanding coastal dumpsite considering climate change - Yijie Wang; Xiaoqing Pi; Vinay Yadav; Abid Hussain; Qian Liu; Yao Wang; Yuliang Guo; Yan Zhang; Xunchang Fei (Waste Management, 2025)

Composition, structure and comprehensive utilization of abalone shell: A review - Man-Yu Li; Yan-Chao Wu; Li Huang; Pi-Xian Gong; Hui-Jing Li (Sustainable Chemistry and Pharmacy, 2025)

TLRs signaling pathway regulation, antibacterial and apoptotic activity of largemouth bass ECSIT during Edwardsiella piscicida infection - Xiangyu Pi; Dong Yan; Yang Xu; Mingzhu Pan; Zisheng Wang; Mingxian Chang; Zhitao Qi (Aquaculture, 2025)

Restoring sweat gland function in mice using regenerative sweat gland cells derived from chemically reprogrammed human epidermal keratinocytes - Jiangbing Xiang; Huating Chen; Hongliang Zhang; Lu Wu; Yan Li; Shuaifei Ji; Wei Pi; Shaoyuan Cui; Lei Dong; Xiaobing Fu; Xiaoyan Sun (Science Bulletin, 2024)

Differential analysis of ovarian tissue between high and low-yielded laying hens in the late laying stage and the effect of LECT2 gene on follicular granulosa cells proliferation - Lin Chen; Xianqiang Li; Yan Wu; Jiaxiang Wang; Jinsong Pi (Molecular Biology Reports, 2024)

Enhancing demulsification efficiency and sustaining constant separation flux in oil/water emulsions via Janus membrane inspired by spider silk - Xiaojing Li; Shouping Xu; Xinjuan Zeng; Yuanyang Yan; Min Zhang; Jie Luo; Pihui Pi; Xiufang Wen (Journal of Environmental Chemical Engineering, 2024)

Characteristics and aging of microplastics in waste activated sludge under persulfate and hydrothermal co-treatment: Impact of solid content and temperature - Yan Wang; Yafei Shi; Longyu Fang; Zhipeng Wang; Pan Wu; Xiong Yang; Xiong Shi; Kewu Pi (Environmental Pollution, 2024)

Effects of dietary supplementation with fermented flaxseed meal on the growth performance, immune function, and intestinal microbiota of growing pigs - Lei Xu; Zixi Wei; Yao Guo; Baozhu Guo; Long Cai; Jingjiao Yan; Lianghua Ma; Wenjuan Sun; Yanpin Li; Xianren Jiang; Xilong Li; Yu Pi (Animal Feed Science and Technology, 2024)

Catalytic oxidation of SO2 in O2-aerated aqueous Solution: superior catalytic capability of KOH/urea-treated biochars and catalytic mechanism - Liu Pi; Yan Shao; Tao Xu; Junru Ma; Yan Li; Xuhui Mao (Chemical Engineering Journal, 2024)

Preliminary Investigation Into the Antidepressant Effects of a Novel Curcumin Analogue (CACN136) In Vitro and In Vivo - Jinglin Chen; Yumeng Wei; Nong Li; Chao Pi; Wenmei Zhao; Yueting Zhong; Wen Li; Hongping Shen; Yan Yang; Wenwu Zheng; Jun Jiang; Zerong Liu; et al. (Molecular Neurobiology, 2024)

Luminescent carbon dots-rooted polysaccharide crosslinked hydrogel adsorbent for sensitive determination and efficient removal of Cu2+ - Jingkun Li; Liying Wang; Guoyong Jiang; Yuqi Wan; Jiahua Wang; Yan Li; Fuwei Pi (Food Chemistry, 2024)

Effect of zinc(II) and caustic content on the decomposition of sodium aluminate solutions and relevance to the Bayer process - Lei Xu; Wen-mi Chen; Yan-jun Zhang; Shang Fan; Jian-qing Pi; Ming-li Wang (Hydrometallurgy, 2024)

Anti-obesity effect of fucoidan from Laminaria japonica and its hydrothermal degradation product - Hai-Yan Lu; Xue Zhao; Tong-Jie Liu; Xi Liang; Mao-Zhen Zhao; Xiao-Ying Tian; Hua-Xi Yi; Pi-Min Gong; Kai Lin; Zhe Zhang; Lan-Wei Zhang (Food Bioscience, 2024)

Iodide and sulfite synergistically accelerate the photo-reduction and recovery of As(V) and As(III) in sulfite/iodide/UV process: Efficiency and mechanism - Mengchao Zhou; Tingting You; Zelong Yan; Xiayu Zhu; Minhan Pi; Xiangfeng Zeng; Shaofeng Wang; Yongfeng Jia (Water Research, 2024)

Arsenic biogeochemical cycling association with basin-scale dynamics of microbial functionality and organic matter molecular composition - Xianjun Xie; Lu Yan; Shige Sun; Kunfu Pi; Jianbo Shi; Yanxin Wang (Water Research, 2024)

Long-term cadmium exposure induces epithelial-mesenchymal transition in breast cancer cells by activating CYP1B1-mediated glutamine metabolic reprogramming in BT474 cells and MMTV-Erbb2 mice - Jingdian Li; Peng Gao; Mingke Qin; Junhua Wang; Yan Luo; Ping Deng; Rongrong Hao; Lei Zhang; Mindi He; Chunhai Chen; Yonghui Lu; Qinlong Ma; et al. (Science of The Total Environment, 2024)

Transparent self-cleaning coatings repellent to ultralow surface tension liquids in extreme environments - Liying Liu; Min Zhang; Yuanyang Yan; Yahong Zhou; Shuangfeng Wang; Pihui Pi; Xiufang Wen; Yu Qian; Lei Jiang (Chemical Engineering Journal, 2024)

Composite aerogel incorporating low temperature phase change microcapsules for enhanced thermal insulation - Bin Yan; Min Li; Honglang Lu; Menghan Pi; Jiahao Mu; Wei Cui; Rong Ran (Chemical Engineering Journal, 2024)

Long-term exposure to polystyrene microplastics induces hepatotoxicity by altering lipid signatures in C57BL/6J mice - Jiawen Tao; Ping Deng; Min Lin; Chunhai Chen; Qinlong Ma; Lingling Yang; Wenjuan Zhang; Yan Luo; Siyu Chen; Huifeng Pi; Zhou Zhou; Zhengping Yu (Chemosphere, 2024)

Chronic cadmium exposure triggered ferroptosis by perturbing the STEAP3-mediated glutathione redox balance linked to altered metabolomic signatures in humans - Ping Deng; Jingdian Li; Yonghui Lu; Rongrong Hao; Mindi He; Min Li; Miduo Tan; Peng Gao; Liting Wang; Huihui Hong; Jiawen Tao; Muxue Lu; et al. (Science of The Total Environment, 2023)

Systematical Evaluation of the Structure-Cardiotoxicity Relationship of 7-Azaindazole-based PI3K Inhibitors Designed by Bioisosteric Approach - Tianze Wu; Yi Chen; Chengbin Yang; Mingzhu Lu; Fang Geng; Jianhua Guo; Yan Pi; Yun Ling; Jun Xu; Tong Cai; Lei Lu; Yaming Zhou (Cardiovascular Toxicology, 2023)

Environmental cadmium exposure facilitates mammary tumorigenesis via reprogramming gut microbiota-mediated glutamine metabolism in MMTV-Erbb2 mice - Yang Yue; Huadong Zhang; Ping Deng; Miduo Tan; Chengzhi Chen; Bo Tang; Jingdian Li; Fengqiong Chen; Qi Zhao; Ling Li; Rongrong Hao; Hui Wang; et al. (Science of The Total Environment, 2023)

Hydrogel-based intelligent greenhouse films for simultaneous fogging prevention and indoor environmental monitoring - Honglang Lu; Huanxiong Liang; Jianle Liu; Hui Zhou; Menghan Pi; Min Li; Bin Yan; Wei Li; Wei Cui; Rong Ran (Chemical Engineering Journal, 2023)

Surfactant-assisted air flotation: A novel approach for the removal of microplastics from municipal solid waste incineration bottom ash - Jiaqi Chai; Yafei Shi; Yan Wang; Xiong Yang; Kewu Pi; Andrea R. Gerson (Science of The Total Environment, 2023)

Transcriptomics integrated with metabolomics unravels the interweaving of inflammatory response and 1-stearoyl-2-arachidonoyl-sn-glycerol metabolic disorder in chronic cadmium exposure-induced hepatotoxicity - Rongrong Hao; Heng Xiao; Hui Wang; Ping Deng; Yang Yue; Jingdian Li; Yan Luo; Li Tian; Jia Xie; Mengyan Chen; Zhou Zhou; Fengqiong Chen; et al. (Environmental Toxicology and Pharmacology, 2023)

Fabrication of foxtail millet prolamin/caseinate/chitosan hydrochloride composite nanoparticles using antisolvent and pH-driven methods for curcumin delivery - Xiao Chen; Yan-Chao Wu; Liu-Hong Qian; Yu-He Zhang; Pi-Xian Gong; Wei Liu; Hui-Jing Li (Food Chemistry, 2023)

Long-term cadmium exposure impairs cognitive function by activating lnc-Gm10532/m6A/FIS1 axis-mediated mitochondrial fission and dysfunction - Ping Deng; Huadong Zhang; Liting Wang; Sheng Jie; Qi Zhao; Fengqiong Chen; Yang Yue; Hui Wang; Li Tian; Jia Xie; Mengyan Chen; Yan Luo; et al. (Science of The Total Environment, 2023)

Correction to: LncRNA GATA3‑AS1 promoted invasion and migration in human endometrial carcinoma by regulating the miR‑361/ARRB2 axis - Yu‑xi Liu; Shuo Yuan; Xiao‑jing Liu; Yan‑xi Huang; Pin Qiu; Jie Gao; Gao‑pi Deng (Journal of Molecular Medicine, 2022)

Correction to: LncRNA GATA3‑AS1 promoted invasion and migration in human endometrial carcinoma by regulating the miR‑361/ARRB2 axis - Yu‑xi Liu; Shuo Yuan; Xiao‑jing Liu; Yan‑xi Huang; Pin Qiu; Jie Gao; Gao‑pi Deng (Journal of Molecular Medicine, 2022)

LncRNA GATA3-AS1 promoted invasion and migration in human endometrial carcinoma by regulating the miR-361/ARRB2 axis - Yu-xi Liu; Shuo Yuan; Xiao-jing Liu; Yan-xi Huang; Pin Qiu; Jie Gao; Gao-pi Deng (Journal of Molecular Medicine, 2022)

The role of Th17 cells: explanation of relationship between periodontitis and COPD? - Jiaohong Liu; Yuanting Ouyang; Zhiyi Zhang; Siyi Wen; Yixing Pi; Ding Chen; Zhikang Su; Zitian Liang; Lvhua Guo; Yan Wang (Inflammation Research, 2022)

Talaromyces Marneffei Infection in an HIV-Negative Child with a CARD9 Mutation in China: A Case Report and Review of the Literature - Cheng-yan You; Fang Hu; Si-wei Lu; Dan-dan Pi; Feng Xu; Cheng-jun Liu; Yue-qiang Fu (Mycopathologia, 2021)

Drought tolerance in high-generation transgenic maize inbred lines overexpressing the betaine aldehyde dehydrogenase gene - He Zhao; Qi Zhang; Mo Zhang; Yu-Kun Jin; Zhen-Zhong Jiang; Nan Jiang; Qi Wang; Jing Qu; Shu-Yan Guan; Pi-Wu Wang (Cereal Research Communications, 2021)

Construction of a new plant expression vector and the development of maize germplasm expressing the Aspergillus ficuum phytase gene PhyA2 - Peng Jiao; Wen-Ya Yuan; Han-Dan Zhao; Jing Qu; Pi-Wu Wang; Shu-Yan Guan; Yi-Yong Ma (Genetic Resources and Crop Evolution, 2021)
Phytases, which belong to a special category of orthophosphoric monoester phosphohydrolases, degrade inositol hexaphosphate to produce lower-grade inositol phosphate derivatives and inorganic phosphate. Thus, phytases may improve phosphorus utilization, eliminate the anti-nutrient properties of phytic acid, and mitigate environmental pollution due to phosphorus contamination. In this study, we constructed a new root-specific expression vector by inserting the Aspergillus ficuum phytase gene PhyA2 into pCAMBIA3301-ZmGLU1P-Nos. The subsequent molecular analysis confirmed that six T 4 generation transgenic plants carried and expressed PhyA2 . A quantitative real-time PCR analysis indicated PhyA2 was highly expressed in the transgenic roots. Additionally, the phytase activity was 10.9-fold higher in the transgenic roots (peak activity of 5.432 U/g) than in the control roots. Moreover, compared with the control rhizosphere, the organic phosphorus content in the rhizosphere of the transgenic plants decreased significantly (by up to 5.21 mg/kg). An agronomic trait analysis indicated that PhyA2 expression can increase maize seed weight by up to 25.8 g. Therefore, the integration of PhyA2 into the maize genome can enhance the ability of maize plants to use the phosphorus compounds in soil, while also improving the plant growth status and increasing the seed yield.

Synthesis of natural product inulavosin via Ga(OTf) 3 -Catalyzed Hetero Diels–Alder Dimerization of salicyl alcohol derivative - Pi-Xian Gong; Hui-Jing Li; Meirong Wang; Yun-Fei Cheng; Yan-Chao Wu (Natural Product Research, 2019)

Isolation, culture, and identification of duck intestinal epithelial cells and oxidative stress model constructed - Hao Zhang; Fang Chen; Zhen-Hua Liang; Yan Wu; Jin-Song Pi (In Vitro Cellular & Developmental Biology - Animal, 2019)

Discovery of a novel multifunctional carbazole–aminoquinoline dimer for Alzheimer's disease: copper selective chelation, anti-amyloid aggregation, and neuroprotection - Xiao Zhang; Ying Wang; Sheng-nan Wang; Qiu-he Chen; Ya-lin Tu; Xiao-hong Yang; Jing-kao Chen; Jin-wu Yan; Rong-biao Pi; Yan Wang (Medicinal Chemistry Research, 2018)

TRPV1 attenuates intracranial arteriole remodeling through inhibiting VSMC phenotypic modulation in hypertension - Ming-Jie Zhang; Yun Liu; Zi-Cheng Hu; Yi Zhou; Yan Pi; Lu Guo; Xu Wang; Xue Chen; Jing-Cheng Li; Li-Li Zhang (Histochemistry and Cell Biology, 2017)

The critical role of ABCG1 and PPARγ/LXRα signaling in TLR4 mediates inflammatory responses and lipid accumulation in vascular smooth muscle cells - Xiaojie Cao; Lili Zhang; Chunhai Chen; Qingsong Wang; Lu Guo; Qinlong Ma; Ping Deng; Gang Zhu; Binghu Li; Yan Pi; Chunyan Long; Lei Zhang; et al. (Cell and Tissue Research, 2017)

Impaired SIRT1 promotes the migration of vascular smooth muscle cell-derived foam cells - Ming-Jie Zhang; Yi Zhou; Lei Chen; Xu Wang; Yan Pi; Chun-Yan Long; Meng-Jiao Sun; Xue Chen; Chang-Yue Gao; Jing-Cheng Li; Li-Li Zhang (Histochemistry and Cell Biology, 2016)

USPIO assisting degradation of MXC by host/guest-type immobilized laccase in AOT reverse micelle system - Yu-Xiang Yang; Na Pi; Jian-Bo Zhang; Yan Huang; Ping-Ping Yao; Yan-Jie Xi; Hong-Ming Yuan (Environmental Science and Pollution Research, 2016)

Concentrations and health risk assessment of metal(loid)s in indoor dust from two typical cities of China - Yiwen Li; Lu Pi; Wenli Hu; Mengqin Chen; Yan Luo; Zhi Li; Shijun Su; Zhiwei Gan; Sanglan Ding (Environmental Science and Pollution Research, 2016)

Grain Size Distribution and Health Risk Assessment of Metals in Outdoor Dust in Chengdu, Southwestern China - Mengqin Chen; Lu Pi; Yan Luo; Meng Geng; Wenli Hu; Zhi Li; Shijun Su; Zhiwei Gan; Sanglan Ding (Archives of Environmental Contamination and Toxicology, 2016)

An overview of potential molecular mechanisms involved in VSMC phenotypic modulation - Ming-Jie Zhang; Yi Zhou; Lei Chen; Yan-Qin Wang; Xu Wang; Yan Pi; Chang-Yue Gao; Jing-Cheng Li; Li-Li Zhang (Histochemistry and Cell Biology, 2016)

Amino Acid, Fatty Acid, and Metal Compositions in Edible Parts of Three Cultured Economic Crabs: Scylla paramamosain, Portunus trituberculatus , and Eriocheir sinensis - Ke-Ji Jiang; Feng-Ying Zhang; Yan Pi; Li-Li Jiang; Zhong-Li Yu; Dan Zhang; Man-Man Sun; Lu-Jiao Gao; Zhen-Guo Qiao; Ling-Bo Ma (Journal of Aquatic Food Product Technology, 2014)

Association between estrogen receptor alpha c.454-397T>C and c.454-351A>G and ischemic stroke risk: a systematic review and meta-analysis - Bing-Hu Li; Li-Li Zhang; Yan-Wei Yin; Yan Pi; Lu Guo; Qing-Wu Yang; Chang-Yue Gao; Chuan-Qin Fang; Jing-Zhou Wang; Jing Xiang; Jing-Cheng Li (Molecular Biology Reports, 2012)

Association between paraoxonase 2 Ser311Cys polymorphism and ischemic stroke risk: a meta-analysis involving 5,008 subjects - Bing-Hu Li; Li-Li Zhang; Yan-Wei Yin; Yan Pi; Qing-Wu Yang; Chang-Yue Gao; Chuan-Qin Fang; Jing-Zhou Wang; Jing-Cheng Li (Molecular Biology Reports, 2012)

Optimisation of preparation conditions and properties of phytosterol liposome-encapsulating nattokinase - Xu-Yan Dong; Fan-Pi Kong; Gang-You Yuan; Fang Wei; Mu-Lan Jiang; Guang-Ming Li; Zhan Wang; Yuan-Di Zhao; Hong Chen (Natural Product Research, 2012)

Alternative splicing and genetic diversity of the white collar-1 (wc-1) gene in cereal Phaeosphaeria pathogens - Ericka Yen-Hsin Chiu; Ying-Hong Lin; Wei Wu; Qijian Song; Pi-Fang Linda Chang; Ling-Yan Gao; Chun-Chi Chou; Peter P. Ueng (European Journal of Plant Pathology, 2010)

Promotion of nicotine biosynthesis in transgenic tobacco by overexpressing allene oxide cyclase from Hyoscyamus niger - Keji Jiang; Yan Pi; Rong Hou; Lili Jiang; Xiaofen Sun; Kexuan Tang (Planta, 2009)

Molecular cloning and expression profiling of the first specific jasmonate biosynthetic pathway gene allene oxide synthase from Lonicera japonica - Keji Jiang; Yan Pi; Rong Hou; Hainian Zeng; Zhuoshi Huang; Zheng Zhang; Xiaofen Sun; Kexuan Tang (Molecular Biology Reports, 2009)

Sample digestion for determining chloramphenicol residues in carp serum and muscle - Zhi-Yong Huang; Qing-Pi Yan; Qiang Zhang; Ai-Hong Peng (Aquaculture International, 2009)